A Case of Fronto-Temporal Dementia (FTD) Masquerading as Mood Disorder. Issue 1 (1st January 2018) - Pospos, Sarah; Xi, Min; Chen, Guanjie; Zhang, Ruiguo; Tan, Qingrong; Baskys, Andrius
ABSTRACT: A 56-year old Chinese female was referred to an academic medical center with atypical, treatment-resistant depression that continued for approximately 3 years after her sister's death. Comprehensive evaluation including neurocognitive testing, EEG, spinal tap, HIV testing and brain MRI revealed behavioral variant of fronto-temporal dementia (bvFTD) with significant frontal and temporal lobe atrophy.This patient's unusual clinical presentation emphasizes the overlap between depression and bvFTD, and underlines the importance of prompt, accurate diagnosis to minimize often-ineffective pharmacological interventions and caregiver burnout.